The Alexander Legend: An Example of Syriac Apocalyptic Literature in the Dawn of Islam - Aljaž Krajnc (Edinost in Dialog, 2022)
The article introduces the Syriac Alexander Legend, a text that was written in the context of the Byzantine imperial propaganda and aimed to present the Byzantine Empire as the fourth empire from Daniel’s prophecy on the four kingdoms. In the first chapter, the author analyzes the prophecy on the succession of the four kingdoms contained in the Book of Daniel. The second chapter is dedicated to the analysis of Aphrahat’s Demonstration on Wars, which is presented as an example of Syriac political theology. In the third chapter, the author sketches the story line of the Alexander legend and offers a Slovenian translation of the selected passages of the Alexander Legend. In the fourth chapter, a short commentary on the Alexander legend is provided. The commentary addresses the origins, basic theological concepts, and authorship of the Alexander legend. In the conclusion of the paper, the author highlights the importance of the Alexander Legend for the subsequent apocalyptic literature in the Christian as well as in the Islamic world.